A Comprehensive Review of Bioelectrical Impedance Analysis and Other Methods in the Assessment of Nutritional Status in Patients with Liver Cirrhosis. (13th August 2017) - Cichoż-Lach, Halina; Michalak, Agata
Abstract : It is assumed that approximately 24–66% of patients with liver cirrhosis develop malnutrition. Numerous pathological processes lead to serious disorders of nutritional status in this group of patients. Malnutrition in the course of liver cirrhosis is associated with increased morbidity, complications, and low quality of life. Under these conditions, detection of malnutrition is of crucial importance. This review explores the complex mechanisms that lead to malnutrition in the course of liver cirrhosis and focuses on methods used in the assessment of nutritional status in cirrhotic patients. Among others, the role of bioelectrical impedance is highlighted. This noninvasive tool is promising and quite an accurate method of estimating body composition.